Peran Kameramen LPP TVRI Sulawesi Selatan Dalam Meningkatkan Pemahaman Etika Pengambilan Gambar di Kalangan Milenial - Karmila Karmila; Andriansyah Andriansyah (Departement of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2022)
The purpose of this study was to determine the role of LPP TVRI South Sulawesi cameramen in increasing the understanding of shooting ethics among millennials and the inhibiting factors in the application of shooting ethics among millennials. The research method used is descriptive qualitative. Data was obtained through interviews, observation, and documentation. The interview technique was conducted on 30 informants consisting of 10 employees of LPP TVRI South Sulawesi, 10 millennials who have been directly involved in LPP TVRI South Sulawesi, and 10 people who have never been directly involved in LPP TVRI South Sulawesi. The results of the study indicate the role of LPP TVRI South Sulawesi cameramen in improving the understanding of shooting ethics This is felt by millennials who have been directly involved in LPP TVRI South Sulawesi. But for millennials who have never been directly involved in LPP TVRI South Sulawesi, did not feel the role of the cameraman even though almost all of the informants stated that they did not know the ethics of taking pictures. Lack of application of ethics shooting among millennials creates a low awareness of respecting the right to privacy.